Effect of Inulin DP on Various Properties of Sugar-Free Dark Chocolates Containing Lactobacillus paracasei and Lactobacillus acidophilus - Konar, Nevzat; Palabiyik, Ibrahim; Toker, Omer Said; Polat, Derya Genc; Sener, Sinem; Akcicek, Alican; Sagdic, Osman (WALTER DE GRUYTER GMBH, 2017)
In the present study, the effect of different polymerization degree of inulin on the quality parameters of conventional and sugar-free dark chocolate products as well as on the vitality of probiotics used in the chocolates were investigated. To produce sugar-free dark chocolates prepared with the addition of maltitol, Lactobacillus paracasei/L. acidophilus and inulin with DP higher than 23 and lower than 10 were used as probiotic and pre-biotic agents, respectively. After 90 day of storage, more than 6 log cfu/25 g probiotics were observed in the chocolates produced by supplementing of 9 log cfu/25 g probiotics. Considering the probiotic level for both conventional and sugar-free dark chocolate, the highest probiotic level was observed in the samples prepared from L. acidophilus and inulin with DP < 10. In addition, inulin with DP < 10 was found as more suitable in terms of rheological characteristics of the samples. Other quality parameters ( texture, colour, melting profile and water activity) changed in narrow range which was allowable when compared with the control samples. Consequently, sugar-free chocolate containing L. paracasei and L. acidophilus could be produced which might satisfy the expectations of the consumers and appropriate to industrial production similar to conventional chocolate. The findings of the present study highlighted the importance of the selection of the most suitable prebiotic/probiotic combination for maximizing probiotic level in the chocolate products.
Keywords: chocolate; maltitol; probiotic; inulin; prebiotic; PARTICLE-SIZE DISTRIBUTION; LACTIC-ACID BACTERIA; MILK CHOCOLATE; RHEOLOGICAL PROPERTIES; TEXTURAL PROPERTIES; PROBIOTIC BACTERIA; SENSORY PROPERTIES; BULKING AGENTS; FAT; SWEETENERS; Food Science & Technology